2009
DOI: 10.1002/pro.29
|View full text |Cite
|
Sign up to set email alerts
|

Investigating protein unfolding kinetics by pulse proteolysis

Abstract: Investigation of protein unfolding kinetics of proteins in crude samples may provide many exciting opportunities to study protein energetics under unconventional conditions. As an effort to develop a method with this capability, we employed ''pulse proteolysis'' to investigate protein unfolding kinetics. Pulse proteolysis has been shown to be an effective and facile method to determine global stability of proteins by exploiting the difference in proteolytic susceptibilities between folded and unfolded proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 21 publications
3
50
1
Order By: Relevance
“…Although we believe this method to be widely applicable, when applying it to new systems, it is important to take into account the limitations of pulse proteolysis, including possible steric hindrance because of biomolecular interactions (16,32). Nevertheless, it should be possible to extend our approach to determine how the ribosome modulates protein folding kinetics by monitoring unfolding rates via pulse proteolysis (33). In addition, given the seemingly important role of quality control at the ribosome in general cellular proteostasis (34), it will be important to know how RNC stability is altered in the presence of ribosome-associated chaperones such as trigger factor (in bacteria) or the ribosome quality control complex (in eukaryotes).…”
Section: Discussionmentioning
confidence: 99%
“…Although we believe this method to be widely applicable, when applying it to new systems, it is important to take into account the limitations of pulse proteolysis, including possible steric hindrance because of biomolecular interactions (16,32). Nevertheless, it should be possible to extend our approach to determine how the ribosome modulates protein folding kinetics by monitoring unfolding rates via pulse proteolysis (33). In addition, given the seemingly important role of quality control at the ribosome in general cellular proteostasis (34), it will be important to know how RNC stability is altered in the presence of ribosome-associated chaperones such as trigger factor (in bacteria) or the ribosome quality control complex (in eukaryotes).…”
Section: Discussionmentioning
confidence: 99%
“…These precedent studies suggested that dSNP HtrA1, which is translated from a transcript containing NvAMD-associated SNPs, may also have an altered protein conformation. To consider this possibility, we subjected WT and dSNP HtrA1 produced in HEK 293T cells to partial proteolysis (8,(48)(49)(50). dSNP HtrA1 was more susceptible to proteolysis than WT HtrA1 was (Fig.…”
Section: Htra1mentioning
confidence: 99%
“…been used previously to determine protein stability (38) and monitor unfolding kinetics (39). Here we show that this technique can also be modified to monitor refolding kinetics and in a double jump experiment.…”
Section: Stability Of the Core Coat Protein And I-domain Compared Witmentioning
confidence: 87%
“…The refolding jump is then initiated by dilution into buffer. Thermolysin pulse proteolysis, which exploits the change in proteolytic susceptibility between folded and unfolded proteins (38,39), was used to measure the amount of native I-domain at varying times after refolding was initiated (Fig. 7b).…”
Section: Stability Of the Core Coat Protein And I-domain Compared Witmentioning
confidence: 99%